Analisis Perbandingan Metode Certainty Factor Dan Teorema Bayes Untuk Mendiagnosa Penyakit Paru-Paru Anak - Sitinjak, Trifave (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Expert systems are one of the fields of artificial intelligence engineering that is quite in demand because of its application in various fields both in the fields of science and business which have proven to be very helpful in making decisions and are very broad in application. One of the applications of the expert system is in the field of medicine which is used to diagnose a disease. Lung disease is a disease that attacks the respiratory system in humans whose incidence rate is quite wide and can attack various ages. infect the respiratory tract and cause the patient to experience shortness of breath. Lung diseases that are often found in everyday life are pneumonia, tuberculosis, bronchitis, common cough accompanied by fever. Diagnosing diseases with an expert system, it is necessary to apply methods to solve the problem. The method applied is the certainty factor method, the Bayes theorem method. The use of these two methods will be compared to measure the level of expert confidence and the level of probability of symptoms that are likely to suffer from lung disease so that the most appropriate and best method for diagnosis can be known.